Mobile Money and Financial Inclusion in Sub- Saharan Africa: the Moderating Role of Social Networks - Okello Candiya Bongomin, George; Ntayi, Joseph M.; Munene, John C.; Akol Malinga, Charles (Journal of African Business, 2018)
The purpose of this article is to test the moderating effect of social networks in the relationship between mobile money usage and financial inclusion in rural Uganda. The results revealed that there is a significant and positive moderating effect of social networks in the relationship between mobile money usage and financial inclusion in rural Uganda. Besides, mobile money usage and social networks have direct and significant effects on financial inclusion in rural Uganda. Thus, the findings suggest that existence of social networks of strong and weak ties among mobile money users promote financial inclusion in rural Uganda. Previous studies have concentrated only on investigating the impact of mobile money in promoting financial inclusion in developing economies, especially in Sub-Saharan Africa. However, this particular study introduces the moderating effect of social networks in the relationship between mobile money usage and financial inclusion in rural Uganda, which seems to be sparse and lacking in literature.
Keywords: Mobile money services; Financial inclusion; Rural Uganda; Sub-Saharan Africa; Network ties